(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2024)
This research develops an IoT-based billing system for managing billiard table usage, aimed at addressing various issues arising from the use of manual systems. Currently, many billiard table rental businesses still rely on manual methods for transaction recording and lamp control, which increases the risk of rate manipulation, inaccurate transaction reports, and inefficient resource management. The manual process also adds to the workload of operators, especially when billiard tables are located far apart. The developed system utilizes Bluetooth sensors and a web app to automatically control the billiard table lamps, thereby reducing manipulation and improving operational efficiency. Testing shows that the system accurately calculates the usage fees and controls the lamp status based on commands from the web server. As a result, the system not only enhances the accuracy of cost calculation and the reliability of billiard table management but also provides a better user experience. Thus, the implementation of this IoT-based billing system offers significant benefits in optimizing billiard center management.